The role of level and function of High Density Lipoprotein (HDL) in Cardiovascular Diseases - Malihe Aghasizadeh (Journal of Birjand University of Medical Sciences, 2020)
High-density lipoprotein (HDL) is a set of particles with heterogeneous structures that have different functions due to various compounds including surface charge, size, lipid, and protein compounds. Several prospective epidemiological studies have demonstrated that there is a clear inverse relationship between serum HDL concentration and risk of coronary heart disease, despite this relationship, clinical evidence has only challenged the usefulness of higher levels of HDL-C in predicting the risk of cardiovascular diseases (CVD) and have proven that the structure of HDL is altered and loosed function. Therefore, extensive research is needed to identify new agents and biomarkers to improve HDL function and reduce the risk of cardiovascular disease. Given that the most important function of HDL is to transfer excess cholesterol from peripheral tissues and macrophage cells through a receptor called ABCA1 and direct it to the liver, plays an important role in protecting the formation of atherosclerotic plaque. This molecule can provide a strong protective effect against oxidative damage caused by free radicals with intermittent inhibition of the production of pro-inflammatory oxidized lipids in the intima layer of arteries. There is an inverse relationship between the ability to efflux cholesterol and the prevalence of CVD. The ability to remove cholesterol from macrophages by HDL, it is a crucial criterion for determining HDL performance, and it has a strong inverse relationship with carotid intima-media thickness and coronary artery stenosis in angiography independent of HDL level